Public Private Partnership in Social Sphere: Models Review - Liliia V Matraeva; Alexey A. Konov; Alexey V. Belyak; Sergey G. Erokhin; Ekaterina S. Vasyutina (International Journal of Economics and Financial Issues, 2016)
Growing social pressure on economy is a global trend nowadays due to constant increase of elderly population not accompanied by respective world economy growth. One of ways to respond to global challenges became new model of social & infrastructure investments called Public Private Partnership. In this article authors analyze specifics of Public Private Partnerships in social sphere and reasons why they came up to the world’s agenda. Such areas as health protection, sports, education, culture, utilities are treated as social. Main goal of majority of partnerships is social as well and due to this such projects have low income rates and high risks associated. Nevertheless, in the article models of effective Public Private Partnerships are illustrated and analyzed in depth. The most promising models out of all options are selected and conclusion for the need of special tax regulation for the PPP projects is made.